Pakej pembelajaran sistem enjin diesel - Jaharah A. Ghani,; Ramniza Mat Rani, (1997)
The process of designing a diesel engine learning package is described, covering all the aspects from equipment to the programming language which are used to develop the system. This package is developed to help users understand how the diesel engine system works. Besides it could be used as a teaching aided tool to help the instructor at the higher learning institutions. Such package could also be resided into internet system, which is useful for distance learners. It is an informative package. The information covers all aspects of component, systems and fault-finding related to the diesel engine operations. The package was developed using Schooner Version 2.01